Academic Motivation and Self Regulated Learning Strategies in Online Language Education across Culturally Diverse Student Populations - Desmaliza Desmaliza; Sri Suharti; Dina Destari (International Forum of Researchers and Lecturers, 2024)
This study examines the relationship between self regulated learning (SRL) strategies and academic motivation among students engaged in online language education, with a particular focus on how cultural diversity influences these factors. SRL strategies, such as goal setting, self monitoring, and time management, are crucial for maintaining motivation and improving learning outcomes, especially in online settings that require high levels of student autonomy. The study found a strong positive correlation between intrinsic motivation and the use of SRL strategies. Students who were intrinsically motivated to learn demonstrated better use of SRL strategies, leading to improved academic performance. Furthermore, the study explored how cultural diversity impacted the application of SRL strategies, revealing that students from collectivist cultures often emphasized collaboration and effort, while students from individualistic cultures focused more on autonomy and personal achievement. These cultural differences influenced how students engaged with SRL strategies and maintained their motivation throughout their online language courses. The findings underscore the importance of considering cultural diversity when designing online language education programs. Culturally responsive teaching practices that acknowledge students' cultural backgrounds can enhance motivation, foster better use of SRL strategies, and improve learning outcomes in diverse online classrooms. The study highlights the need for further research that explores the interaction between different cultural groups, expands sample sizes, and investigates other motivational factors, such as self efficacy and achievement goals, to develop more effective and inclusive online language education strategies.